2011
DOI: 10.1101/cshperspect.a004564
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Signaling in Synapse-to-Nucleus Communication

Abstract: Changes in the intracellular concentration of calcium ions in neurons are involved in neurite growth, development, and remodeling, regulation of neuronal excitability, increases and decreases in the strength of synaptic connections, and the activation of survival and programmed cell death pathways. An important aspect of the signals that trigger these processes is that they are frequently initiated in the form of glutamatergic neurotransmission within dendritic trees, while their completion involves specific c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 307 publications
(515 reference statements)
0
113
0
1
Order By: Relevance
“…Compared with what is known about signaling pathways involved in postsynaptic development (Ebert and Greenberg, 2013;Hagenston and Bading, 2011;Mabb and Ehlers, 2010;Shen and Cowan, 2010;Stamatakou and Salinas, 2014;Tolias et al, 2011), less is known about signaling pathways guiding presynaptic differentiation. The presynaptic contribution of individual signaling pathways has been studied using broad inhibition or overactivation: PI3K/AKT (MartinPe帽a et al, 2006;Cuesto et al, 2011), extracellular signal-related kinase (ERK)/mitogen-activated protein kinase (MAPK) (Li et al, 2002;Kushner et al, 2005;Nakata et al, 2005;Wairkar et al, 2009;Giachello et al, 2010) and PLC纬 (Yoshida et al, 2009) have been all proposed to be involved in presynaptic development.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with what is known about signaling pathways involved in postsynaptic development (Ebert and Greenberg, 2013;Hagenston and Bading, 2011;Mabb and Ehlers, 2010;Shen and Cowan, 2010;Stamatakou and Salinas, 2014;Tolias et al, 2011), less is known about signaling pathways guiding presynaptic differentiation. The presynaptic contribution of individual signaling pathways has been studied using broad inhibition or overactivation: PI3K/AKT (MartinPe帽a et al, 2006;Cuesto et al, 2011), extracellular signal-related kinase (ERK)/mitogen-activated protein kinase (MAPK) (Li et al, 2002;Kushner et al, 2005;Nakata et al, 2005;Wairkar et al, 2009;Giachello et al, 2010) and PLC纬 (Yoshida et al, 2009) have been all proposed to be involved in presynaptic development.…”
Section: Introductionmentioning
confidence: 99%
“…Our lab focuses on the inositol 1,4,5-trisphosphate receptor (IP 3 R), which forms a Ca 2+ release channel located in the endoplasmic reticulum (ER) membrane. Upon binding of both IP 3 and Ca 2+ to the cytosolic activating sites of the receptor, the IP 3 R channel opens to liberate Ca 2+ sequestered within the ER lumen. The release of Ca 2+ may remain spatially restricted to a small cluster of IP 3 Rs to generate a local cytosolic microdomain of Ca 2+ (Ca 2+ puff 4 ) or, depending on the proximity of neighboring clusters of IP 3 Rs, may propagate throughout a cell by recruiting multiple puff sites through a process of Ca 2+ -induced Ca 2+ -release (CICR) 5,6 .…”
Section: +mentioning
confidence: 99%
“…One way through which Ca 2+ can act in such a diverse manner is through the different spatial and temporal patterns of Ca 2+ signals a cell can generate. For example global elevations in cytosolic [Ca 2+ ] trigger contraction in smooth muscle tissue 2 whereas smaller, localized transient elevations (local Ca 2+ microdomains) stimulate gene expression essential for learning and memory 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[Ca 2+ ] i stimulates TRPC6 activity and inhibits TRPC7 activity via Ca 2+ /calmodulin [42] . On the other hand, Ca 2+ infl ux through dendritic outgrowth [43] . It has been reported that CaMKII伪, CaMKII尾, and CaMKIV can be activated by Ca 2+ influx through TRPC channels.…”
Section: Dendritic Developmentmentioning
confidence: 99%